2005
DOI: 10.1139/h05-107
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heat Removal Through the Hand on Metabolism and Performance During Cycling Exercise in the Heat

Abstract: Catalogue DataHsu, A.R.; Hagobian, T.A.; Jacobs, K.A.; Attallah, H.; and Friedlander, A.L. (2005). Effects of heat removal through the hand on metabolism and performance during cycling exercise in the heat. Can. J. Appl. Physiol. 30 (1)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 30 publications
2
42
0
Order By: Relevance
“…Time to exhaustion was ∼5.5 minutes longer in the control condition compared to the palm cooling condition. In contrast, another study reported that palm cooling improves 30 km cycling time trial performance in the heat (32°C) with 4 minutes (6.6%, ES = 1.54) 61 . Therefore, the effects of palm cooling are still unclear and future studies are warranted.…”
Section: Per-coolingmentioning
confidence: 95%
“…Time to exhaustion was ∼5.5 minutes longer in the control condition compared to the palm cooling condition. In contrast, another study reported that palm cooling improves 30 km cycling time trial performance in the heat (32°C) with 4 minutes (6.6%, ES = 1.54) 61 . Therefore, the effects of palm cooling are still unclear and future studies are warranted.…”
Section: Per-coolingmentioning
confidence: 95%
“…The arteriovenous anastomoses (AVAs) and venous plexuses in the palms of the hands and the soles of the feet are effective mechanisms for heat dissipation when core body temperature rises (3,4,9,10,17). A device previously described (11) is used to apply a 35-to 45-mmHg subatmospheric pressure to an entire hand to draw blood into the hand and increase the filling of the venous plexus underlying the palmar surface. A heat sink applied to that palm extracts heat and cools the venous blood.…”
mentioning
confidence: 99%
“…The exercise protocol in the current study was of a much greater intensity for a shorter duration than the protocols that have reported a significant cooling effect of the RTX. For example, in the study conducted by Hsu et al (2005), subjects cycled at a 60% VO 2 peak for approximately 60 minutes, while in the study by Grahn et al (2005), subjects walked at moderate rate until their HR reached 90% of the predicted maximum, which occurred between 34 and 57 minutes of continuous exercise. The intensity of the exercise protocol in the present study was very high.…”
Section: Discussionmentioning
confidence: 99%
“…The intended result is a greater heat exchange than with cooling alone. Two investigations (Grahn et al, 1999, Hsu et al, 2005 have reported that use of the RTX enhanced cooling and/or mitigated thermal stress during exercise more successfully than no cooling (Hsu et al, 2005) or hand cooling alone (Grahn et al, 1999). Additionally, the company that manufacturers the RTX (AVAcore Technologies, Ann Arbor, MI) has reported anecdotal evidence of athletes increasing repetitive set training volumes by extremely large amounts when using the CoreControl™ between sets and/or intervals.…”
Section: Introductionmentioning
confidence: 99%